REGIONAL POLICY OF SOCIAL INFRASTRUCTURE DEVELOPMENT IN THE CONTEXT OF IMPROVING THE QUALITY OF LIFE OF THE POPULATION OF THE CARPATHIAN REGION OF UKRAINE - Vasyltsiv , Taras; Bil , Mariana; Bachynska , Mariіa (Socio-economic relations in the digital society, 2021)
Abstract. The article deals with the basic characteristics of the living standards of population. The workconsolidates aspects of the social infrastructure development in a region. The priorities of social infrastructure andpeculiarities of its elements performance in Carpathian area are described. It primarily concerns mountainouslocation of a great number of settlements. Therefore, the specificity of the social infrastructure development inthat region involves remoteness of many settlements from administrative and economic centers, problematicaccess to some services of social and economic character for conformable living. Peculiarities of the socialinfrastructure development in Carpathian area and their impact of the living standards of population directlydepend on climate conditions, particularly weather and natural phenomena. Considering peculiarities of thesocial infrastructure in Carpathian area, it is determined that organization of social infrastructure in the regionhas its territorial specificity and should consider the balance and relationship of its elements performance in thesystem of economic complex of the region; its complex nature should be supported at the state, regional, and locallevels; as well as the required number and optimal size of the objects to supply population with social servicesshould be supplied; compliance of the actual conditions and technical equipment with the population’s demandsshould be provided. The research substantiates directions and tools of the regional policy concerning the socialinfrastructure development in context of improvement of the population’s living standards, which significantlyinfluence involvement of ecological and social determinants of its improvement, because the primary task ofthe social infrastructure is to create an appropriate environment for human living that covers such spheres aseducation, healthcare, culture, sport, residential and public economies. The author of the research identifies expectedoutcomes from implementation of the instruments of the social infrastructure development in terms ofimprovement of the living standards of the Carpathian area population in terms of the following areas: effectiveuse of health and recreational potential of the Ukrainian Carpathians; development of cross-border cooperationin the field of improving social infrastructure and environmental protection; transition to smart-oriented developmentof housing and communal services; improving the transit potential of the Carpathian region; preservationand improvement of the cultural environment.Keywords: social infrastructure, living standards of population, Carpathian area of Ukraine, directions andtools of regional policy, social and ecological determinants.JEL Classification I31, I38, R19, R58Formulas: 0; fig.: 1; tabl.: 1; bibl.: 10.
Keywords: social infrastructure; iving standards of population; Carpathian area of Ukraine; directions and tools of regional policy; social and ecological determinants